Measurement and analysis of K-shell lines of silicon ions in laser plasmas. (5th June 2018) - Han, Bo; Wang, Feilu; Zhong, Jiayong; Liang, Guiyun; Wei, Huigang; Yuan, Dawei; Zhu, Baojun; Li, Fang; Liu, Chang; Li, Yanfei; Zhao, Jiarui; Zhang, Zhe; et al.
Abstract : We present laboratory measurement and theoretical analysis of silicon K-shell lines in plasmas produced by Shenguang II laser facility, and discuss the application of line ratios to diagnose the electron density and temperature of laser plasmas. Two types of shots were carried out to interpret silicon plasma spectra under two conditions, and the spectra from 6.6 Å to 6.85 Å were measured. The radiative-collisional code based on the flexible atomic code (RCF) is used to identify the lines, and it also well simulates the experimental spectra. Satellite lines, which are populated by dielectron capture and large radiative decay rate, influence the spectrum profile significantly. Because of the blending of lines, the traditional G value and R value are not applicable in diagnosing electron temperature and density of plasma. We take the contribution of satellite lines into the calculation of line ratios of He- [STIX]x1D6FC lines, and discuss their relations with the electron temperature and density.